Flotel Europa - Tomić, Vladimir (Denmark, 2015)
In 1992 a wave of refugees from the war in Bosnia and Herzegovina reached Denmark. With refugee camps completely full, the Red Cross pulled a giant ship into the canals of Copenhagen. The ship, Flotel Europa, became a temporary home for a thousand people waiting for decisions on their asylum applications. Among them was a young 12 year old boy, Vladimir, who fled Sarajevo together with his mother and older brother. They spent two years in the limbo of Flotel Europa. Two decades later, Vladimir Tomić takes us on a journey of growing up on this ship filled with echoes of the war - and other things that make up an adolescence. The coming-of-age story is juxtaposed with personal VHS archive material shot by refugees who shared the "space-time vacuum" of the Flotel.
Danish-Serbian co-production. Film also on HDD Verzio11/12 located: M22 R17 S2 R4
Verzio Film Festival Submission
Keywords: Documentary films